PENERAPAN MEDIA PEMBELAJARAN “BUKU EKSPRESIKU” BERBASIS PROJECT BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN MENULIS KALIMAT SEDERHANA SISWA KELAS II SDN NGADIRGO 03 - Siti Purningsih Farida Sari; Panca Dewi Purwati (STKIP Subang, 2025)
This study aims to describe the implementation of the “Buku Ekspresiku” learning media based on Project-Based Learning (PjBL) and its effectiveness in improving simple sentence writing skills among second-grade students at SDN Ngadirgo 03. A mixed-method sequential explanatory design was used, with data collected through observations, interviews, writing tests, and documentation. The results indicate that “Buku Ekspresiku” increased student motivation and their ability to express personal experiences in written form. The average score improved from 74.5 to 85.1, and classical completeness rose from 42.8% to 85.7%. Writing aspects also improved, including content relevance (87.5%), sentence structure (85%), and vocabulary choice (82.5%), although capitalization and punctuation still require guidance. These findings demonstrate that the PjBL-based “Buku Ekspresiku” is effective in supporting meaningful, contextual, and engaging writing learning for elementary students. Keywords: Buku Ekspresiku, PjBL, simple sentence writing